ANALISIS KOMPETENSI APARATUR PEMERINTAH DESA DALAM PERUMUSAN KEBIJAKAN DESA (Suatu Studi di Tiyuh Sidomakmur Kabupaten Tulang Bawang Barat) - Eko Budi Sulistio; Simon Sumanjoyo Hutagalung; M Irsyad Fadoli (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2023)
Before village regulations are discussed jointly with the BPD, village officials draft village regulations. Village officials have a very important role in preparing quality village policy designs. Therefore, village officials must have adequate competence in drafting village regulations. The purpose of this study was to analyze the Competence of the Sidomakmur Village Government Apparatus in Compiling Village Policies (Village Regulations) and to analyze the competency weaknesses of the Sidomakmur village government apparatus in formulating village policies (village regulations). This research is a descriptive qualitative research using data collection methods by interviews and documentation studies. The results of the study show that the Sidomakmur Village apparatus does not yet have good enough competencies to formulate a village policy. The competencies that are still lacking are academic competence and technical competence. This is because the majority of village apparatus only graduated from high school and they also have good competence in using computers. The recommendation that the author gives is to provide scholarships to officials to pursue higher education and organize training in the use of technology and information such as computers.